New version of Bäcklund transformations in Euclidean 3-space - Sariaydin M.T.; Körpınar, Talat (John Wiley and Sons Ltd, 2019)
In this paper, we study the Bäcklund transformations for the adjoint curve in the Euclidean 3-space. Firstly, it is obtained some essential equations of the Bäcklund transformation. After this, we give a new theorem, the Bäcklund transformations for the adjoint curve in Euclidean 3-space. © 2018 John Wiley & Sons, Ltd.
Keywords: Adjoint curve; Bäcklund transformations; Frenet frame